Sources of uncertainty in hydrological climate impact assessment: a cross-scale study - Hattermann, Fred; Vetter, Tobias; Breuer, Lutz; Su, Buda; Daggupati, Prasad; Donnelly, Chantal; Fekete, Balazs; Flörke, Martina; Gosling, Simon N.; Hoffmann, Peter; Liersch, Stefan; Masaki, Yoshimitsu; et al. (IOP Publishing, 2018)
Climate change impacts on water availability and hydrological extremes are major concerns as regards the Sustainable Development Goals. Impacts on hydrology are normally investigated as part of a modelling chain, in which climate projections from multiple climate models are used as inputs to multiple impact models, under different greenhouse gas emissions scenarios, which are resulting in different amounts of global temperature rise. While the goal is generally to investigate the relevance of changes in climate for the water cycle, water resources or hydrological extremes, it is often the case that variations in other components of the model chain obscure the effect of climate scenario variation. This is particularly important when assessing the impacts of relatively lower magnitudes of global warming, such as those associated with the aspirational goals of the Paris Agreement. In our study, we use ANOVA (ANalyses Of VAriance) to allocate and quantify the main sources of uncertainty in the hydrological impact modelling chain. In turn we determine the statistical significance of different sources of uncertainty. We achieve this by using a set of 5 climate models and up to 13 hydrological models, for 9 large scale river basins across the globe, under 4 emissions scenarios. The impact variable we consider in our analysis is daily river discharge. We analyze overall water availability and flow regime, including seasonality, high flows and low flows. Scaling effects are investigated by separately looking at discharge generated by global and regional hydrological models respectively. Finally, we compare our results with other recently published studies. We find that small differences in global temperature rise associated with some emissions scenarios have mostly significant impacts on river discharge – however, climate model related uncertainty is so large that it obscures the sensitivity of the hydrological system.